The Influence of Entrepreneur’s Personal Characteristics on SMES Performance Mediated by Entrepreneurial Orientation - Lukiastuti, Fitri; Harsono, Pramudi; Hadi, Dwi Prastiyo; Pariyanti, Eka; Astutik, Mardi; Sunarsi, Denok; Hayati, Feb Amni; Goso (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the effect of entrepreneur's personal characteristics (need for achievement, need for cognition and internal locus of control) on the business performance of batik SMEs mediated by entrepreneurial orientation at batik SMEs in Semarang. The questionnaire was prepared using a 5 point Likert Scale. The number of samples that were collected from 100 SMEs batik owners/managers. The analytical tool used is Path Analysis and testing the effect of mediation using the Sobel test. From the results of the analysis show that the variable need for achievement, need for cognition and internal locul of control have positive and significant effect on the entrepreneurial orientation variable. The variable need for achievement, need for cognition and entrepreneurial orientation has a positive and significant effect on the performance of batik SMEs. The internal locus of control variable does not have a significant effect on business performance. Entrepreneurial orientation variable is able to mediate the relationship between personal characteristics of entrepreneurs with the business performance of batik SMEs.